(untitled) (Journal of Libya for geographical studies, 2025)
Morocco has a rich and diverse forest cover, which plays an effective role in achieving the country’s economic and social development and maintaining the balance of forest ecosystems in general. This natural cover faces a number of challenges and constraints as a result of the combination of several factors, including drought, which is mainly caused by the phenomenon of climate change that the planet is witnessing, in addition to random and irrational human intervention in dealing with the forest. These factors and others have negatively affected the development of the national forest cover, which has begun to decline, which necessitated the search for effective and efficient solutions within the framework of a national forest management strategy 2020-2030 with the aim of preserving the balance of the Moroccan forest and ensuring its sustainability. This article aims to shed light on the status of the forest cover in Morocco and the risks that threaten it, highlighting the efforts made by the state to manage various risks, and evaluating the effectiveness of these efforts in preserving the national forest heritage and protecting it from all factors of deterioration.